2023
DOI: 10.1001/jamaophthalmol.2023.0270
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorohexyloctane Eye Drops for Dry Eye Disease Associated With Meibomian Gland Dysfunction in Chinese Patients

Abstract: ImportanceMeibomian gland dysfunction (MGD) is a leading cause of evaporative dry eye disease (DED). Medical and surgical management for DED is limited; therefore, new treatment options are sought.ObjectiveTo evaluate the efficacy and safety of SHR8058 (perfluorohexyloctane) eye drops in Chinese patients with DED associated with MGD through 57 days.Design, Setting, and ParticipantsThis was a randomized, multicenter, double-masked, saline-controlled, phase 3 clinical trial conducted from February 4, 2021, to Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Short-term efficacy and safety were consistently demonstrated in the 8-week phase 2 SEECASE, phase 3 GOBI, and phase 3 MOJAVE studies, as well as a phase 3 study conducted in China, in patients with DED associated with MGD. 18 21 In KALAHARI, patients were administered PFHO for 52 weeks; thus, patients who were randomized to PFHO in GOBI were exposed to a cumulative 60 weeks of PFHO treatment during the combined GOBI and KALAHARI study periods. Long-term use of PFHO 4 times daily was safe and well tolerated in patients in the KALAHARI study, with a safety profile consistent with that reported in previous short-term studies of PFHO.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Short-term efficacy and safety were consistently demonstrated in the 8-week phase 2 SEECASE, phase 3 GOBI, and phase 3 MOJAVE studies, as well as a phase 3 study conducted in China, in patients with DED associated with MGD. 18 21 In KALAHARI, patients were administered PFHO for 52 weeks; thus, patients who were randomized to PFHO in GOBI were exposed to a cumulative 60 weeks of PFHO treatment during the combined GOBI and KALAHARI study periods. Long-term use of PFHO 4 times daily was safe and well tolerated in patients in the KALAHARI study, with a safety profile consistent with that reported in previous short-term studies of PFHO.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term use of PFHO 4 times daily was safe and well tolerated in patients in the KALAHARI study, with a safety profile consistent with that reported in previous short-term studies of PFHO. 18 21 During the year-long treatment period, no single ocular AE occurred at an incidence ≥2.0%, and ocular AEs were considered treatment-related in fewer than half of the patients. There was a low rate of instillation site reaction in this study (1.0%), which confirms the favorable tolerability previously reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations